2013
DOI: 10.1093/annonc/mdt151
|View full text |Cite
|
Sign up to set email alerts
|

The standard tangential fields used for breast irradiation do not allow optimal coverage and dose distribution in axillary levels I–II and the sentinel node area

Abstract: TgFs provide a limited coverage of the axilla and the SNLB area. This information should be considered when only TgFs are planned to target the axilla in patients with a positive SLN without ALND. Standardization of locoregional radiotherapy in this situation is urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…In fact, the lower part of the axilla is currently irradiated and receives a nearly therapeutic dose, depending on the upper limit of the tangential fields to the breast or chest wall. 23 A meta-analysis by van Wely et al 24 showed that external-beam radiotherapy to the breast was associated with a lower axillary recurrence rate compared to that in patients who did not receive it as part of initial therapy. Although it may not be considered therapeutic, 25 the dose delivered to the region in which the SLNs are normally found could well influence the natural evolution of residual tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the lower part of the axilla is currently irradiated and receives a nearly therapeutic dose, depending on the upper limit of the tangential fields to the breast or chest wall. 23 A meta-analysis by van Wely et al 24 showed that external-beam radiotherapy to the breast was associated with a lower axillary recurrence rate compared to that in patients who did not receive it as part of initial therapy. Although it may not be considered therapeutic, 25 the dose delivered to the region in which the SLNs are normally found could well influence the natural evolution of residual tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors were the first to publish prospective data concerning SLN biopsy area coverage using a protocol of systematic intraoperative clip placement in that region. Data collected from 12 patients showed a mean dose of 13 Gy, with only 1 patient experiencing full dose levels [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades several studies focused on the evaluation of the axillary lymph node dose after treatment with whole breast radiotherapy with 2 TgF [6][7][8][9][10][11][12][13][14][15]. Regarding modern tridimensional radiation delivering techniques, it is currently accepted that therapeutic doses are not really delivered to the axilla [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…In practice, there is significant unintentional irradiation at least to level I of the ipsilateral axilla even with standard tangents [21]. This might contribute to the unexpectedly low axillary recurrence rate after SLNB alone in the ACOSOG Z0011 trial despite a 27% rate of non-SLN metastasis in the control arm [14].…”
Section: What Is the Best Management Of Cn0pn1(sn) Breast Cancer Patimentioning
confidence: 99%